Diversification of Agricultural Activities: Entrepreneurial Strategy and Market Aspects - Vukovič, Goran; Raspor, Andrej; Papler, Drago; Miklavčič, Nejka (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Strategic planning of complementary farm activities requires an assessment of development conditions, market analysis and an understanding of the competitive environment. The case study farm, with a long-standing tradition and loyal customers, applies an entrepreneurial approach by diversifying into fruit processing, producing jams, juices and syrups to generate additional income and employment opportunities. A SWOT analysis and an evaluation of market opportunities and risks highlight the key strengths, challenges and competitive advantages of the new activity. The strategic business plan includes product programmes, financial projections and performance indicators, demonstrating that diversification is feasible, economically sustainable and market-attractive, provided the emphasis remains on innovation, product quality and meeting customer needs.